Exploring neural markers of language processing using fNIRS in typically developed children and children with Developmental Language Disorder - Papoutselou, Efstratia (2023)
Background: Developmental language disorder (DLD) is a life-long condition with no clear biological causes that affects approximately 8% of the population. The diagnosis currently relies on behavioural testing that is not reliably performed on children younger than school age. Consequently, the diagnosis and treatment of DLD is often delayed until after children enter formal education. Early work in the field suggests that neural markers of language processing could be used to develop an objective diagnostic tool that will allow for accurate and early identification of DLD in preschool years and thus access to early interventions. Here we propose the use of a novel non-invasive neuroimaging technique called functional near infrared spectroscopy (fNIRS) to identify neural markers of language processing in children with DLD. Additionally, we argue that to understand atypical language processing, it is imperative to also investigate typical cortical activations in response to language processing to establish the developmental trajectories of the language network. Parallel to these studies we also investigate patterns of neural synchrony during parent-child interactions. Speech and language development in children is thought to rely on successful parent-child interactions, however, little is known regarding the underlying neural mechanisms from which they arise.